Comparative effectiveness of anthracycline-containing chemotherapy in United States veterans age 80 and older with diffuse large B-cell lymphoma. Issue 3 (May 2015) - Carson, Kenneth R.; Riedell, Peter; Lynch, Ryan; Nabhan, Chadi; Wildes, Tanya M.; Liu, Weijian; Ganti, Arun; Roop, Ryan; Sanfilippo, Kristen M.; O'Brian, Katiuscia; Liu, Jingxia; Bartlett, Nancy L.; et al.
Abstract Objectives While anthracycline-based treatment can cure diffuse large B-cell lymphoma, most patients over age 80 do not receive doxorubicin due to toxicity concerns. This study evaluated this practice, as patients age 80 and older are largely excluded from clinical trials. The primary outcome of interest was overall survival. Secondary outcomes included treatment-related mortality and anthracycline dose intensity. Materials and Methods We assembled a cohort of 530 newly diagnosed diffuse large B-cell lymphoma patients age 80 or older diagnosed within United States Veterans Health Administration. Treatment and survival information were obtained to determine associations between anthracycline use, dose intensity, treatment-related mortality and overall survival. Results Of the 530 patients, 285 received systemic treatment and 193 received an anthracycline. After controlling for potential confounders, rituximab decreased mortality (hazard ratio, 0.62; 95% confidence interval [CI]: 0.44–0.88), while doxorubicin was not significantly associated with mortality (hazard ratio, 0.87; 95% CI: 0.64–1.17). Completion of treatment with anthracycline dose intensity ≥ 85% of expected was only 14%. Patients treated with anthracycline dose intensity < 85% had better one year survival compared to those treated at ≥ 85% (70% vs. 59%, p = 0.029). Conclusion These results suggest that full dose anthracycline therapy may be less important in the treatment of diffuse large B-cell lymphoma patients over age 80. The low frequency of completion of full dose intensity treatment suggests that standard doses are an unrealistic standard of care for patients this age. Alternate treatment strategies and risk stratification should be considered for these patients.